Alpha 1 antitrypsin phenotypes and alcoholic pancreatitis. Issue 8 (August 1991) - Haber, P S; Wilson, J S; McGarity, B H; Hall, W; Thomas, M C; Pirola, R C
Abstract : Altered frequencies of alpha 1 antitrypsin phenotypes have been reported in patients with chronic pancreatitis, suggesting a possible genetic basis for individual susceptibility to this disease. Alpha 1 antitrypsin phenotypes, with particular regard to alcoholic pancreatitis, were studied. Patients with alcoholic pancreatitis were compared with alcoholic control subjects with no history of pancreatic disease. Serum alpha 1 antitrypsin concentrations were raised in pancreatitis patients sampled within one month of an acute attack of pancreatitis, but otherwise values were similar to those of control subjects. There were no significant differences in alpha 1 antitrypsin phenotypes between alcoholics with pancreatitis and alcoholic control subjects. This study of alpha 1 antitrypsin phenotypes provides no evidence of an inherited susceptibility to alcoholic pancreatitis.